Ameliorative effects of nano-selenium against NiSO4-induced apoptosis in rat testes. (2nd September 2019) - Zhang, Xiaotian; Gan, Xiaoqin; E, Qiannan; Zhang, Qiong; Ye, Yixing; Cai, Yunyu; Han, Aijie; Tian, Minmin; Wang, Yixuan; Wang, Caixia; Su, Li; Liang, Changhao
Abstract: Nickel (Ni) is a common environmental pollutant, which has toxic effects on reproductive system. Nowadays, nano-selenium (Nano-Se) has aroused great attention due to its unique antioxidant effect, excellent biological activities and low toxicity. The aim of this study was to explore the protective effects of Nano-Se on NiSO4 -induced testicular injury and apoptosis in rat testes. Nickel sulfate (NiSO4 ) (5 mg/kg b.w.) was administered intraperitoneally and Nano-Se (0.5, 1, and 2 mg Se/kg b.w., respectively) was given by oral gavage in male Sprague–Dawley rats. Histological changes in the testes were determined by H&E staining. The terminal deoxynucleotidyl transferase-mediated dUTP nick end-labeling (TUNEL) assay and immunohistochemistry were performed to evaluate the apoptosis in testes. Expression levels of mitochondrial apoptosis-related genes and proteins were analyzed by RT-qPCR and Western blot. The results showed that Nano-Se improved lesions of testicular tissue induced by NiSO4 . Nano-Se significantly alleviated NiSO4 -induced apoptosis in rat testes, as well as significantly downregulated the Bak, cytochrome c, caspase-9 and caspase-3 and upregulated Bcl-2 expression levels, all of which were involved in mitochondria-mediated apoptosis. Altogether, we concluded that Nano-Se may potentially exert protective effects on NiSO4 -induced testicular injury and attenuate apoptosis, at least partly, via regulating mitochondrial apoptosis pathways in rat testes.